Effects of Bentonite Activation Methods on Chitosan Loading Capacity - Tao Yu; Chengtun Qu; Daidi Fan; Renjun Xu (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
The adsorption capacity of bentonite clay for heavy metal removal from wastewater can be significantly enhanced by a high loading of chitosan on the surface. In order to enhance the chitosan loading, we tested activating bentonite clay by three methods prior to chitosan loading: sulfuric acid, calcination, and microwave treatments. Meanwhile, several parameters during chitosan loading, namely the initial chitosan concentration, stirring speed, reaction time, temperature, and pH value were investigated. Our results indicate that chitosan is attached to bentonite clay through intercalation and surface adsorption according to X-ray Diffraction (XRD), Scanning Eelectron Microscopy (SEM), and Fourier Transform Infrared Spectroscopy (FTIR) analyses. The maximum chitosan loading on 200-mesh raw bentonite clay (126.30 mg/L) was achieved under the following conditions: the initial chitosan concentration of 1000 mg/L, the stirring speed of 200 rpm, pH of 4.9, 60 min of reaction time, and temperature of 30 °C. The chitosan loading was further increased to 256.30, 233.70, and 208.83 mg/g, when using bentonite clay activated through 6 min of microwave irradiation (800 W), 10 % sulfuric acid treatment, and calcinations at 600 °C, respectively. When the chitosan loading was increased from 34.76 to 233.7 mg/g, the removal percentages of Cu(II), Cr(VI), and Pb(II) were improved, respectively from 78.90 to 95.5 %, from 82.22 to 98.74 %, from 60.09 to 86.18 %.